Ludwig Senfl: Motets For Four Voices (A-I). New Senfl Edition 1 - Senfl, Ludwig, approximately 1486-1542 or 1543 (Denkmäler der Tonkunst in Österreich., 2021)
Ludwig Senfl - key figure in the generation of composers between Heinrich Isaac and Orlando di Lasso - began his career in 1498 at the court of Emperor Maximilian I, before he worked at the court of Duke Wilhelm IV in Munich from 1523. Much appreciated by his contemporaries, his central position in early music historiography was anchored by J. N. Forkel and A. W. Ambros. Despite the outstanding quality of Senfl's work, a large part of his oeuvre has not yet been available in a modern edition. The New Senfl Edition (NSE) closes this gap and offers a comprehensive overview of the composer's work on the basis of the latest research. The first two volumes of the NSE present for the first time the entire surviving corpus of the four-part motets, whose wide textual and compositional range demonstrates how the composer internalized international musical trends and developed them further in an innovative way. Ludwig Senfl - a key figure in the generation of composers between Heinrich Isaac and Orlando di Lasso - began his career in 1498 at the court of Emperor Maximilian I, before working at the court of Duke Wilhelm IV in Munich from 1523 onwards. Highly esteemed by his contemporaries, his central role in early music historiography was later cemented through the writings of J. N. Forkel and A. W. Ambros. Despite the outstanding quality of Senfl's work, the majority of his oeuvre has never been made available in a modern edition. The New Senfl Edition (NSE) aims to close this gap by offering a comprehensive overview of this composer's oeuvre based on the latest findings in research. The first two volumes of the NSE present for the first time his complete extant body of four-voice motets, which demonstrate how Senfl internalized international trends in music composition and developed them in innovative ways.